Correlation between stability and energy variations in control strategies for mobile base robot with manipulators subjected to external disturbances. (6th May 2019) - Son, Changman
The correlation between stability and energy variations in control strategies for a mobile base robot with manipulators subjected to external disturbances is introduced. The correlation results can be used to stabilize and control problems when a mobile base robot is subjected to various types of external disturbances. This is because different robot system energy values display different stability distribution curves. Mobile base robot stability based on varying system's energy is described. Two control strategies, computed force/torque and adaptive compensators, are applied to minimize uncertainties accompanied by the robot's movements. The two compensators are then compared by simulating applied external disturbances, such as mobile base tipping motion and load mass changes on the robot end-effector. A comprehensive comparison with other methods is also described. The proposed technique is a useful tool in the maintenance of the degree of control and stability of the system and has various applications in the mobile robot tasks including choosing and placing operations, maneuvering around the workspace with protruding obstacles on sinuous shape paths, and manufacturing tasks.